2012
DOI: 10.1021/nl204414u
|View full text |Cite
|
Sign up to set email alerts
|

High Efficiency Graphene Solar Cells by Chemical Doping

Abstract: We demonstrate single layer graphene/ n-Si Schottky junction solar cells that under AM1.5 illumination exhibit a power conversion efficiency (PCE) of 8.6%. This performance, achieved by doping the graphene with bis(trifluoromethanesulfonyl)amide, exceeds the native (undoped) device performance by a factor of 4.5 and the best previously reported PCE in similar devices by a factor of nearly 6. Current-voltage, capacitance-voltage and external quantum efficiency measurements show the enhancement to be due to the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
652
6
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 897 publications
(685 citation statements)
references
References 24 publications
15
652
6
1
Order By: Relevance
“…Moreover, graphene‐based solar cells are also the subjects of photovoltaic studies 188. To improve the efficiency of DSSCs, a wide‐bandgap semiconductor is needed that would be able to adsorb active dyes and transport the injected electrons into an electrical circuit.…”
Section: Foreseen Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, graphene‐based solar cells are also the subjects of photovoltaic studies 188. To improve the efficiency of DSSCs, a wide‐bandgap semiconductor is needed that would be able to adsorb active dyes and transport the injected electrons into an electrical circuit.…”
Section: Foreseen Applicationsmentioning
confidence: 99%
“…It is because of the broad range of possibility of tuning graphene work function, its superior electrical and optical properties, and, last but not the least, the cost factor. It has been reported that chemical doping of graphene with bis(triofluoromethanesulfpnyl) amide increased the performance of undoped device over four times 188. An increase in the efficiency was linked to the shift in the graphene chemical potentials and to an increase in the carrier density.…”
Section: Foreseen Applicationsmentioning
confidence: 99%
“…Modification of the bandgap and fabrication of large-scale defect-free films are important to achieve TMDC-based solar cell devices with decent efficiency. Recently reported heterojunction solar cells based on TMDC/graphene [163], TMDC/Si [164,165], TMDC/InP [166,167], graphene/Si [168,169] have shown excellent photovoltaic effect and power conversion efficiencies in the visible to infrared region. Solid-phase CVD is commonly used in the fabrication of these 2D semiconductor solar cells.…”
Section: Solar Cellmentioning
confidence: 99%
“…Also, doping the graphene layer has shown to enhance the performance of graphene−silicon solar cells. 11 We can also expect that further increasing V G will increase the barrier height and further enhance the performance of the cell.…”
mentioning
confidence: 98%